Spreading of Islam without any violence in Central, East and West Africa as a case study - Sukdaven, Maniraj (HTS teologiese studies, 2018)
This article studies the violence in the spreading of Islam by conquest and the factors that influenced the development of Islam in Central, East, West and Southeastern Africa. Although the spreading of Islam in these territories had not been done by Islamic conquests, as perpetrated in North Africa and other regions of the Islamic world, the majority of the population in the countries such as Sudan, Chad, Mali, Sierra Leone and Madagascar are Muslims. The results of this article show that the emigrations into these regions had an important role in introducing Islam to the native inhabitants. These emigrations had occurred either freely, through trading by Muslim traders and religious scholars, or forcefully by escaping the political and religious violence perpetrated by Eastern rulers in different areas in Central Africa. In this emigration process, the effect of Islamic scholars, missionaries and Islamic traders together with communication intermediaries among the natives is striking and as the natives became familiar with Islam and Islamic culture, Islam gradually developed after generations of integration between Muslims and native tribes.